What, why and how financial development matters: Evidence of ASEAN-5, Asia-5 and OECD-7 Economies - TAN, Swee Liang (Institutional Knowledge at Singapore Management University, 2021)
This paper analysed the association between bank and capital markets financial development with income per capita in three regions; ASEAN-5 economies (Singapore, Malaysia, Thailand, Philippines, Indonesia), Asia-5 (Japan, China, Hong Kong SAR, South Korea and India) and OECD-7 (Australia, Canada, Denmark, Norway, Sweden, UK and US) covering the period from 2000 to 2017 using panel data analysis. Fixed effect regression models with Driscoll-Kraay standard errors to account for the problem of heteroskedastic and autocorrelated error structure are used. What ASEAN-5 can learn from Asia-5 and OECD-7 experience is that bank size does matter for Asia-5 and OECD-7 despite digital disruptions to their banking systems; yet financial structure that favours banks is negatively associated with income per capita for Asia-5, and importantly, efficient banking system (not bank size alone) drives OECD-7 income per capita. The finding has practical policy implications for a ASEAN-5’s financial sector liberalization programmes that impact the depth, breadth and efficiency of banks and capital markets.